2008
DOI: 10.1104/pp.108.116194
|View full text |Cite|
|
Sign up to set email alerts
|

The Pentratricopeptide Repeat Protein DELAYED GREENING1 Is Involved in the Regulation of Early Chloroplast Development and Chloroplast Gene Expression in Arabidopsis    

Abstract: An Arabidopsis (Arabidopsis thaliana) mutant that exhibited a delayed greening phenotype (dg1) was isolated from a population of activation-tagged Arabidopsis lines. Young, inner leaves of dg1 mutants were initially very pale, but gradually greened and mature outer leaves, more than 3 weeks old, appeared similar to those of wild-type plants. Sequence and transcription analyses showed that DG1 encodes a chloroplast protein consisting of eight pentratricopeptide repeat domains and that its expression depends on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
81
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 65 publications
13
81
0
1
Order By: Relevance
“…6B). A similar transcriptional pattern was observed in the SIG6 knockout mutant Schweer et al, 2006) and other PEP-deficient mutants, such as ptac2/6/12 (Pfalz et al, 2006), clb19 (ChateignerBoutin et al, 2008, dg1 (Chi et al, 2008), and ys1 (Zhou et al, 2008). In addition, a 4.8-kb transcript was also detected for rbcL in ptac14-1 (Fig.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…6B). A similar transcriptional pattern was observed in the SIG6 knockout mutant Schweer et al, 2006) and other PEP-deficient mutants, such as ptac2/6/12 (Pfalz et al, 2006), clb19 (ChateignerBoutin et al, 2008, dg1 (Chi et al, 2008), and ys1 (Zhou et al, 2008). In addition, a 4.8-kb transcript was also detected for rbcL in ptac14-1 (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Recent reports have revealed that mutations in several of the genes encoding TAC components cause deficiencies in PEP-dependent transcription (Pfalz et al, 2006;Garcia et al, 2008;Myouga et al, 2008). As shown in Figure 5, real-time RT-PCR and northern-blot hybridization showed that the expression pattern of plastid genes in ptac14-1 mutants resembles that observed in Drpo mutants (Serino and Maliga, 1998;Krause et al, 2000) and in mutants with lesions in PEP function (Hess et al, 1993;Allison et al, 1996;Hajdukiewicz et al, 1997;Chateigner-Boutin et al, 2008;Chi et al, 2008). These results suggest that pTAC14 is indispensable for the proper function of the PEP transcription machinery.…”
Section: Discussionmentioning
confidence: 87%
“…Fisk et al (1999) first reported a maize PPR gene, (for CHLOROPLAST RNA PROCESSING1), which was implicated by genetic analysis in processing and translation of plastid pet transcripts. Similar effects on plastid transcripts were subsequently observed in other mutants from Arabidopsis (Hashimoto et al, 2003;Meierhoff et al, 2003;Yamazaki et al, 2004;ChateignerBoutin et al, 2008ChateignerBoutin et al, , 2011Chi et al, 2008;Okuda et al, 2009Okuda et al, , 2010Yu et al, 2009;Johnson et al, 2010), rice (Kazama and Toriyama, 2003;Komori et al, 2004;Gothandam et al, 2005), and maize (Williams and Barkan, 2003;Schmitz-Linneweber et al, 2006;Pfalz et al, 2009;Prikryl et al, 2011). Additional evidence for a role of PPR proteins in regulating organelle gene expression has also come from positional cloning of several cytoplasmic male sterility (CMS) restorer genes from petunia (Petunia hybrida; Bentolila et al, 2002) and radish (Raphanus sativus; Brown et al, 2003;Desloire et al, 2003;Koizuka et al, 2003).…”
mentioning
confidence: 68%
“…For example, the Arabidopsis dg1 (for delayed greening1) and ys1 mutants (for yellow seedling1) display a seedling-stage-specific albino and yellow seedling phenotype, respectively. Both DG1 and YS1 encode chloroplast-targeted PPR proteins and YS1 has been shown to be required for editing of rpoB transcripts (Chi et al, 2008;Zhou et al, 2009). The null mutation of the maize PPR2 gene leads to albino seedlings, but does not affect seed development or gametogenesis (Williams and Barkan, 2003).…”
Section: Ysa Encodes a Ppr Protein Essential For Chloroplast Biogenesmentioning
confidence: 99%
See 1 more Smart Citation